An Analysis of Principle of Erga Omnes Partes with Special Reference to the Case of Belgium v. Senegal, 2012 - Rana, Prajwol Bickram (Kathmandu School of Law Review, 2018)
In the Questions relating to the Obligation to Prosecute or Extradite (Belgium v. Senegal case), the International Court of Justice for the very first time declared the country's standing before the court on the basis of erga omnes partes as admissible. The court found that Belgium had the standing to claim the responsibility of Senegal for the alleged breach under the Convention against Torture on the basis of being a party of the same convention. The court described erga omnes partes as the obligation that the state party has to all the other state parties of the convention, the court further stated that it arises due to the common interest of the state parties of a convention. Many sitting judges of the court rejected the reasoning of the majority decision and some gave a dissenting opinion. The present paper assesses the concept of erga omnes partes in the public international law and the legal consequences of erga omnes partes in the future development of public international law. The scope of the present paper is limited within the issue of admissibility of the case with the specific focus on the concept of erga omnes partes and does not deal with the merits or other issues raised before the court.